Reproductive biology of Plesionika narval in the SE Aegean Sea (Eastern Mediterranean) - ANASTASOPOULOU, AIKATERINI; MAKANTASI, PANAGIOTA; KAPIRIS, KOSTAS; SMITH, CHRIS J.; MARAVELIAS, CHRISTOS; KALOGIROU, STEFANOS (Mediterranean Marine Science, 2018)
Plesionika narval is a widespread species of the Pandalidae family, of particular high economic importance for small-scale shrimp trap fisheries in the Dodecanese Islands (SE Aegean Sea). Understanding its biology and reproduction are crucial for stock management. Reproductive biology aspects were studied through data collected during monthly experimental surveys with baited shrimps traps from November 2014 to October 2015 at a depth range of 10 - 150m. A total of 3436 individuals within the size range of 6.46 to 20.20 mm carapace length (CL) was analyzed. Overall, mean female size was significantly higher than mean male size, while the mean size of ovigerous females was higher than that of non-ovigerous females. Mean carapace length of ovigerous and non-ovigerous females was significantly correlated to depth. Ovigerous females were observed throughout the study period; however, monthly proportions revealed April to October as the main reproductive period of the species in the area. The sex ratio showed a clear predominance of females in the shallow depth zone (10-25 m) and was found to be affected by sampling area and depth zone. Immature females were found from November to March. Mature females were found all year round, exhibiting higher percentages in March, June, July and September, coinciding with the main reproductive period. P. narval seemed to spawn more than one time within the annual reproductive cycle. Gonadosomatic index obtained its highest mean values in May, June and September, thus revealing the main reproductive period. Size at first maturity for females was estimated at CL50=11.7 mm.